Network Pharmacology Analysis of Black Turmeric (Curcuma caesia Roxb.) for Diabetic Nephropathy: Exploring Potential Therapeutic Targets - Zakiyyah Qurrotul 'Aini; Muhammad Farid; Tri Wijayanti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Diabetes mellitus is a non-communicable disease with a high prevalence that has the potential to cause chronic complications, such as diabetic nephropathy (ND). Diabetic nephropathy is characterized by microalbuminuria, decreased glomerular filtration rate, and the risk of end-stage renal failure. Conventional treatment with oral hypoglycemic drugs often causes side effects such as hyperkalemia and impaired heart function. This indicates the need for alternative therapies with high effectiveness, low toxicity, and affordable costs. This study explores the potential of black turmeric as a therapeutic agent for diabetic nephropathy through an in-silico approach. The active compounds of black turmeric were analyzed for their pharmacokinetics using SwissADME based on Lipinski's rules. The target proteins of the compounds were obtained through SwissTargetPrediction and compared with ND-encoding proteins from GeneCards using Venny 2.1. Specific proteins were analyzed for protein-protein interactions through STRING and visualized with pharmacological networks using Cytoscape. In-depth analysis was carried out to identify biological pathways through KEGG and molecular activity using WebGestalt. The results showed that black turmeric has 123 specific target proteins for ND, with EGFR and STAT3 as core proteins that play a role in regulating apoptosis, inflammation, and insulin sensitivity. Curcumin showed significant activity on the AGE-RAGE and FoxO pathways, which are relevant for the treatment of ND. This study provides initial insight into the potential of black turmeric as an alternative therapy for diabetic nephropathy